Psikologi Pendidikan Islam: Peran Guru dalam Menanamkan Kecerdasan - Algusni, Ikhwanudin; Masduki, Yusron (Lembaga Yasin AlSys, 2024)
Islamic educational psychology is a scientific study that discusses the human soul innature various points of view based on Islamic studies contained in the Qur'an. Islamic educational psychology discusses and understands individual behavior in an effort to change behavior based on the values of Islamic teachings in personal, social and life through the educational process. Teachers have an important role in the psychology of Islamic education in supporting student development in accordance with Islamic teachings. The aspects of the teacher's role in Islamic education are 1) the teacher plays a role as spiritual formation, 2) the teacher becomes a model of positive behavior, 3) the teacher can relate the delivery of knowledge.